Kemahiran interpersonal kanak-kanak menerusi aktiviti boneka - Loy, Chee Luen; Jamaluddin, Shahrir; Borhan, Lihanna (UPSI, 2013)
Puppets as a visual teaching tool can help children's development especially interpersonal skills. This research is to investigate children attitude change from interpersonal aspect which emphasized on daily activities like playing, learning, eating, speaking and helping each other.